Immigrant Population in a New Host-Region: Differences and Similarities Across Southern European Countries - Antonis Rovolis; Alexandra Tragaki (European Regional Science Association (ERSA), 2006)
During the last two decades, Southern Europe has become a destination region for migrants, as a result of demographic, economic and social developments across Eastern and Southern Europe. A number of common characteristics have been put forward to explain the unexpected and simultaneous transformation of this part of Europe into an appealing destination for new migratory flows. Those common explanatory factors of the reasons why immigrants are attracted to countries in Southern Europe have led to the development of the so-called "Southern European model of migration", while the examination of immigrants' personal characteristics across Greece, Italy and Spain reveals some interesting differences. This paper sheds light on who the immigrants are, their specific characteristics, how they are spatially distributed and the causal factors of this distribution- the latter through the use of regression analysis.
Keywords: 330